Enhancing the Industry Readiness of Fashion Design Graduates: The Role of Universities in Skill Development in Asia (A Literature Review) - Evangeline, Zsa-Zsa; Agustina, Tri Siwi; Vincent, Aurelius (Faculty of Education Universitas Negeri Malang, 2025)
Fashion designers play a crucial role in the fashion industry by creating designs that meet market demands. There are many skills that need to be learned to become a fashion designer, which can be acquired through higher education. This study uses a literature review method to explore how universities prepare aspiring fashion designers for the workforce, particularly in Asia. The study shows that, in Asia, especially in China, fashion design graduates are equipped with both soft and hard skill curricula from universities and have successfully become fashion designers needed by the industry. However, in other countries such as Pakistan, the preparation of graduates is not yet as advanced as in China. The skills and curriculum taught by universities are key factors in shaping a fashion designer's readiness to meet market and industry demands.